55-year old woman with erysipelas - Plagens-Rotman, Katarzyna; Przybylska, Renata; Gerke, Katarzyna; Adamski, Zygmunt; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Erysipelas belongs to the inflammatory erythema of acute course spreading with lymphatic vessels, in which the pathogen (group A β-haemolytic streptococcus) pen- etrates the human system through the extrinsic (skin- damaging) or intrinsic pathway, in particular from nasal mucosa and oral cavity, which in turn leads to infection of the skin and subcutaneous tissue. The frequency of occurrence of erysipelas in European countries is estimated at 9–24 per 10,000 inhabitants [1, 2]. The peak of illness is between 60 and 80 years of age, with women suffering more often than men. In some cases, a predisposition to the disease among newborns and young children is also observed [3].